Developing a conceptual relationship between web service supply chain entities - Krithika, V.; Sekaran, K.; Kaur, Arshinder; Rajendran, C. (2011)
Globalization has led to a new class of service apart from the services that are offered offline and semionline (in which case part of the service transactions are online and part of it offline) as a result of collaboration of static entities resulting in static service supply chains. The advent of enablers like Service Oriented Architecture and development of web service applications has enabled online / dynamic service supply chain networks (SSCNs) formed by dynamic collaboration of many serving entities. The entities in web SSCNs are interdependent and the performance of one entity impacts the performance of other entities as well as overall performance of service network. It is important to study the relationship and dependency between each entity of web SSCNs. Once the relationship is identified, it will help in devising some composite performance indicator for the entire service supply chain considering the interests of service providers and clients. We take a scenario based illustration of such online service supply chains to show the feasibility of the concept© 2011 IEEE.